The Relevance and Proportionality of Political Rights Revocation in Corruption Cases: A Juridical Analysis of Decision No. 10/Pid.Sus-TPK/2018/Jkt.Pst - Endi Arofa; Susanto; Lely Zakiah Gunsar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The revocation of political rights has emerged as a significant additional sanction in corruption cases adjudicated in Indonesia's Corruption Court. This article examines the relevance and proportionality of such a sanction through a juridical analysis of Decision No. 10/Pid.Sus-TPK/2018/Jkt.Pst. Using normative legal research methods and a case study approach, the study explores the legal basis, judicial reasoning, and implications of the court’s decision to revoke political rights. The analysis considers both national legal provisions, particularly Article 18 of Law No. 31 of 1999 as amended by Law No. 20 of 2001, and international human rights principles. Findings indicate that while the revocation aims to prevent corrupt individuals from re-entering political office, its application must meet criteria of necessity, proportionality, and legal certainty. The decision in this case reflects an effort to balance deterrence with the protection of constitutional rights. The study concludes that political rights revocation can be justified when applied in a targeted and reasoned manner, especially for public officials who have betrayed public trust.